2014
DOI: 10.5123/s1679-49742014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Internações por condições sensíveis à atenção primária à saúde em uma região de saúde paulista, 2008 a 2010

Abstract: Objetivo: descrever as internações por condições sensíveis à atenção primária (ICSAP) na região de saúde de São José do Rio Preto, no interior paulista. Métodos: estudo descritivo cuja fonte de dados foi o Sistema de Informações Hospitalares do Sistema Único de Saúde (SIH/SUS) no período 2008-2010. Resultados: o coeficiente de ICSAP dessa região de saúde foi em torno de 13,0/1000 habitantes a cada ano; os cinco diagnósticos mais frequentes foram insuficiência cardíaca, angina, infecções do aparelho urinário, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
39

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 15 publications
5
27
0
39
Order By: Relevance
“…The NCD epidemic strongly impacts human and social development. The four NCD addressed in this study account for 13% of all hospitalizations observed in the period, confirming the findings of one study 9 conducted in one region of the state of São Paulo, in which CHF, angina, and CD were frequent causes of hospitalizations among people over 40 years of age and accounted for 71% of the expenses from hospitalizations for ACSC. For this reason, preventive measures should be a priority in the development and investment of state public health policies, as well as in the implementation of chronic disease care networks.…”
Section: Discussionsupporting
confidence: 75%
“…The NCD epidemic strongly impacts human and social development. The four NCD addressed in this study account for 13% of all hospitalizations observed in the period, confirming the findings of one study 9 conducted in one region of the state of São Paulo, in which CHF, angina, and CD were frequent causes of hospitalizations among people over 40 years of age and accounted for 71% of the expenses from hospitalizations for ACSC. For this reason, preventive measures should be a priority in the development and investment of state public health policies, as well as in the implementation of chronic disease care networks.…”
Section: Discussionsupporting
confidence: 75%
“…Estudos corroboram que a diarreia costuma ser uma das principais causas de internação nesta faixa etária e que existe uma associação positiva destas internações com as características da organização do atendimento médico prestado, com o tamanho do município e questões educacionais, logo incrementos na atenção primária podem reduzir a morbidade hospitalar. 13,[23][24] Foi possível observar tal fato no presente estudo, na qual a principal causa de internação hospitalar por causa sensível em menores de 5 anos foram as gastroenterites infecciosas e suas complicações, já com tendência decrescente na maioria dos municípios após 2013, ano de implantação do programa na região, sugerindo o caráter preventivo e educacional proporcionado à população em função da ampliação das ações em saúde na atenção primária.…”
Section: Discussionunclassified
“…The previous study conducted in Pelotas using a shorter list of primary care-sensitive conditions showed that spending on HPCSC represented 4.8% and 14.6% of hospitalization costs in the city 14 . More recently, Ferreira et al 28 showed that spending on HPCSC accounted for 17% of all hospitalizations in São José do Rio Preto, São Paulo.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it can be argued that reducing HPCSC is not only a strategic measure given the lack of resources available, but it can also help the health system save money as well as allow for reinvestment in priority sectors 14,28 . 13,30 .…”
Section: Discussionmentioning
confidence: 99%